Review: Partial Splenic Embolization Outcome on Liver Cirrhosis with Esophageal Varices - Suhartono, Raden; Irsal, Muhammad F. A (UI Scholars Hub, 2022)
Introduction. Liver cirrhosis may be followed by complications such as esophageal varices for 30 days mortality rate up to 15-20%. Partial splenic embolism (PSE) or partial splenic embolization has been developed as a safe and effective alternative therapy for managing bleeding in esophageal varices. This study aims to determine the outcome of PSE in patients with liver cirrhosis with esophageal varices. Method. In this review, the literature search proceeded on three online databases (Cochrane Library, MEDLINE (PubMed), and ScienceDirect) according to PRISMA protocol. Through selections, six articles were included, and all were the reports. Results. Of six reports, three were focused on liver function tests, and the other three were focused on bleeding varices. All were comparing before and after embolization. Conclusion. There is a significant difference in serum cholinesterase and a decreasing incidence of varices bleeding before and after PSE treatment. However, there was no significant difference in serum albumin before and after PSE.